Non-Verbal Signs and Secret Communication as Universal Signs of Intercultural Communication - Muratova, A.N.; Mazhitayeva, Sh.; Sarybayeva, B.Zh.; Kelmaganbetova, A.; Kulibekova, Zh. (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2021)
The article is devoted to the study of the national cognitive nature, the hidden essence of non-verbal techniques. The main purpose of the study is to prove that nonverbal signs are used to convey a confidential message to show that in international communication there is a change in the semantics of nonverbal actions depending on the culture and individual knowledge of each nation. Methods: In human life, in parallel with verbal communication, an experiment was conducted on nonverbal techniques, sometimes used in pure form to convey a secret and hidden message. The article presents an analysis based on a statistical method compared with some kinemes used in a common language. In the studies on non-verbal techniques, it is noted that they perform a crucial function in the relations between people. In this article, in the course of analyzing the nature of nonverbal techniques, we characterized some kinemes used depending on the worldview of the Kazakh people and concluded that their background is directly related to the mystery. Application of the study: The results, the materials, and the conclusions of the work can be used in the history of language, sociolinguistics, and paralinguistic studies, and allow researchers of gesture semantics to explore nonverbal techniques from a new perspective. Scientists-linguists, psychologists have created many works related to the definition of human nature, character, and the place of nonverbal techniques in the speech act. However, it was not said that auxiliary means located outside the language will be used to transmit confidential, non-public information. In this work, we stopped at the place of nonverbal methods of transmitting confidential, hidden information and analyzed the functions in a confidential communication.
Keywords: nonverbal communication; communication; cognition; secret communication; kineme